Quantum size effects in TiO2 thin films grown by atomic layer deposition - Tallarida, Massimo; Das, Chittaranjan; Schmeisser, Dieter (Beilstein Journal of Nanotechnology, 2014)
We study the atomic layer deposition of TiO2 by means of X-ray absorption spectroscopy. The Ti precursor, titanium isopropoxide, was used in combination with H2O on Si/SiO2 substrates that were heated at 200 °C. The low growth rate (0.15 Å/cycle) and the in situ characterization permitted to follow changes in the electronic structure of TiO2 in the sub-nanometer range, which are influenced by quantum size effects. The modified electronic properties may play an important role in charge carrier transport and separation, and increase the efficiency of energy conversion systems.
Keywords: atomic layer deposition (ALD); charge transfer multiplet; covalency; energy conversion; quantum size effects; titanium dioxide (TiO2); water splitting; X-ray absorption spectroscopy (XAS)